Mathematical Modeling of a Solar Drier Temperature Profile - Korkoren , Kenneth; Rotich , Titus; Rotich , Samwel (International Journal of Applied Mathematical Research, 2025)
Food shortages in most countries are not only associated with unfavorable weather conditions, but are also significantly blamed on ineffective post-harvest handling of food. Eminent threats caused by post-harvest losses ‎due to inadequate drying and poor storage is responsible for up to 40-60% losses of agricultural produce each ‎season. One of the mitigation strategies is the provision of sustainable and affordable food drying facilities. The ‎most suitable solution is the use of solar food driers, which can be accessed locally. The optimal performance of ‎a solar food drier depends on the consideration of design parameters and operation guidelines. This research paper models a solar drier to identify significant parameters and simulates to determine their optimal threshold values for the purpose of designing an effective solar drier suitable for dehydrating a variety of agricultural products. The model was formulated using a system of differential equations, to describe dynamics in four ‎distinct compartments of a solar drier, namely; the solar heat collector, the closed loop pipe network circulating ‎thermal fluid, the set of heat exchanger where heat is extracted from the hot liquid to hot drying air, and lastly is ‎the dying chamber with controls of humidity, temperature, mass flow rate and energy balance. The set of solar ‎dryer mathematical model equations was transformed to a MATLAB–SIMULINK model for simulation and ‎parameter estimation. It was found that exposing a solar collector of ηc=0.8 efficiency, with aperture area of ‎Ac=14.4m2 and a fluid capacity of Vc=500l, to solar irradiation of average Ic=5.6637KW/m2 can heat 5000 ‎liters of water from Tin=220C to Tco=700C in 12 hours at a collector’s flow rate of v ̇c=1.128l/s. This ‎heat energy in the thermal fluid can be extracted using a 5m2 heat exchanger to obtain hot air of up to 700C, ‎which can be regulated to the desired temperature depending on the food to be dried.